Analisis Kesalahan Berbahasa Dalam Menulis Teks Narasi Siswa Kelas IV Sekolah Dasar - Khairiatun Nafizah; Tasya Aulia; Chandra Chandra; Ari Suriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The objective of this study is to analyse language faults, including word choice errors (diction), spelling and punctuation problems, and sentence structure errors, in narrative essays written by fourth-grade elementary school pupils. This study employs a qualitative descriptive approach, utilising a case study research style. The study revealed that the most prevalent errors were related to word selection (diction) and the usage of capital letters. According to the findings, Indonesian grade IV instructors should enhance and supplement their teaching on spelling usage and provide instruction on proper sentence patterns in order to enhance students' knowledge. .